Steams-Based Entrepreneur Curriculum Development by Empowering Local Potential for Elementary Students - Rokhmaniyah Rokhmaniyah; Kartika Chrysti Suryandari; Siti Fatimah Siti Fatimah (International Journal of Science and Applied Science: Conference Series, 2020)
This study aims to develop a curriculum model of entrepreneurship curriculum based on Science, Technology, Art, Engineering, Mathematics, and Society (STEAMS) by empowering local potential in Kebumen Elementary School and its application to grow the entrepreneurial spirit of students in Kebumen Elementary School. This research is a Research and Development (R&D) research. The development model follows the Four-D model (Define, Design, Develop, Disseminate). The subjects in this study consisted of 8 elementary schools in Kebumen. The instruments used were test sheets, observation sheets, interview sheets, and questionnaire sheets. Data analysis techniques in this study used quantitative qualitative analysis. The results showed that: 1) The development of an entrepreneurial curriculum model based on STEAMS by empowering local potentials to foster the entrepreneurial spirit of elementary school students was successfully implemented; 2) How to foster students' entrepreneurial spirit by compiling syllabus, lesson plans, student worksheets, teaching materials, media, learning resources, and facilities and infrastructure in an integrated manner in product-based learning, extracurricular activities, and habituation; 3) STEAMS-based entrepreneurship learning can foster the entrepreneurial spirit of elementary school students. It recommends practitioners, researchers and stakeholders to empower entrepreneurship with STEAMS in elementary school.